Incentives For Women to Work Outside the Home: A Field Study in Erbil City - Twana Othman Mohamedamen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Progress and changes in technology, industry and the economy are a major cause of change in the structure and social system of global societies; among these social changes is the increase in the number of women working outside the home. In light of this phenomenon, we conducted this study, "Women's Work Outside the Home", a field study in Erbil. We have set some objectives, including what are the reasons why women work outside the home. The most important barriers to women when working outside the home are challenged, presenting the most important and negative aspects of women's work outside the home. This research is based on two main aspects: theory and the process; and the theoretical aspect consists of three parts, starting with the overall context of the research, including the research problem and the importance and objectives of the research. The first part of two main topics is the explanation of research concepts, scientific terms, and concepts (motivations, working women). The second part includes previous research, and the third part relates to women's work outside the home, including social motivations, economic motives and psychological motivations. The second aspect is practical (field) and includes two sections, the fourth part speaks of the method of research and procedures for field work, such as the analytical descriptive method, the method of surveying the meeting, and taking examples of the type of sample intended. The researcher used the " Questionnaires " to collect information. At a time when the fifth part of the presentation and analysis of research information. At the end of this research, the results of the study were discussed, and some suggestions and recommendations were made on women's work in Kurdish society.